Perancangan Busana Ready-To-Wear Ibu dan Anak dengan Aplikasi Teknik Digital Printing dan Teknik Bordir sebagai Pengembangan Produk Local Brand Crazy Little Party Club - Rahma Putri, Andini; Bastaman, Widia Nur Utami; Ramadhan, Mochammad Sigit (Universitas Ciputra Surabaya, 2024)
The development of local brands is relatively rapid with the presence of the #LocalPride movement on social media, which brings progress to the developing of local products in the fashion sector, especially children’s fashion products. At the Jakarta Fashion Week event in 2022, a well-known local brand, Cottonink, released a collection of mother and child clothing that was welcomed by the public. Therefore, local brands are increasingly choosing the potential for developing children’s products so that mothers can look harmonious with their children. The Crazy Little Party Club brand, which has the characteristics of applying playful motifs with digital printing techniques, is also interested in developing various ready-to-wear clothing products for mothers and children. The research used a qualitative method, with data collection techniques, namely literature study, observation, interviews, and exploration. This research aims to create new product variations in the Crazy Little Party Club brand by applying motifs using digital printing techniques that have become its trademark to mother and child products. In addition to digital printing techniques, researchers will also combine them with embroidery techniques that are popularly used in children’s clothing so that it is expected to offer product novelty in the market. The product design method applies the SCAMPER method, adjusting to the design concept made. The research output resulted in the design of ready-to-wear clothing products for mothers.